Marine chondroitin sulfate of defined molecular weight by enzymatic depolymerization. (1st February 2020) - Valcarcel, Jesus; García, Míriam R.; Sampayo, Lucía F.; Vázquez, José Antonio
Highlights: Condroitin sulfate (CS) from five fish species is enzymatically depolymerized. Decrease in molecular weight (Mw) is fitted to a pseudo-mechanistic model. The model allows to establish conditions of reaction to obtain CS of tailored Mw. The main sulfation features of marine CS remain in the depolymerised fragments. Abstract: Chondroitin sulfate (CS) is a sulfated glycosaminoglycan with diverse biological activities, which are influenced by molecular weight (Mw) and sulfation pattern. In the present work, we take advantage of the characteristic high Mw of fish CS (51–70 kDa) to obtain lower Mw fragments with hyaluronidase and chondroitinase ABC. With this aim, we present a pseudo-mechanistic model capable of reproducing the decrease in Mw of CS from five different fish species over 24 h at four enzyme to substrate ratios. The fitting parameters of the model for each species allow to establish conditions of reaction to produce CS of the desired Mw. Furthermore, the main features of the sulfation pattern of fish CS remain in the depolymerized fragments, highlighting the feasibility of the proposed approach.